Interfaces and social mediation: Disputes over land regularization in the Upper Uruguay at the beginning of the 21st century (Misiones, Argentina) - Kostlin, Laura Andrea; García, Ariel Oscar (Geografares, 2026)
This research analyzes the dynamics of social mediation observed at the institutional interface between an organization of land-owning families and the provincial state administration in the Upper Uruguay River basin, Misiones Province (Argentina) during the early 21st century. Adopting a qualitative-ethnographic approach based on primary sources (participant observation, semi-structured interviews) and secondary data (academic literature, public documents, etc.) the study reconstructs various significant “place-events” within the process. Among the main findings, it is evident that the land regularization process: a) constitutes a field of social mediation between landholders and the state (statalness), where collective agency and technical-political capacity of the landholders prove crucial for sustaining the demand and influencing the state agenda; and b) the demand for regularization exhibits the reproduction of  limitations and contradictions of a fragmented and bureaucratic state, which hinders the crystallization of comprehensive processes for land access.
Keywords: interfaces; social mediation; land regularization